2012
DOI: 10.1186/1471-2458-12-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of complications from comprehensive abortion care services in Nepal

Abstract: BackgroundIn March 2002, Nepal's Parliament approved legislation to permit abortion on request up to 12 weeks of pregnancy. Between 2004 and 2007, 176 comprehensive abortion care (CAC) service sites were established in Nepal, leading to a rise in safe, legal abortions. Though monitoring systems have been developed, reporting of complications has not always been complete or accurate. The purpose of this study was to report the frequency and type of abortion complications arising from CAC procedures in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
3
18
1
Order By: Relevance
“…The restrictive laws in relation to abortion in most developing countries lead women to use unsafe practices of abortion, competing for a larger occurrence of infections and genital trauma. In this study, the major complication related to abortion was infection, and these data are consistent with other studies that were investigated to severe maternal morbidity associated with abortion 9,12 . The frequency of complications was higher among women with gestational age above 12 weeks and this may reflect the delay in recognizing the pregnancy as well as, the difficulty to access health services.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The restrictive laws in relation to abortion in most developing countries lead women to use unsafe practices of abortion, competing for a larger occurrence of infections and genital trauma. In this study, the major complication related to abortion was infection, and these data are consistent with other studies that were investigated to severe maternal morbidity associated with abortion 9,12 . The frequency of complications was higher among women with gestational age above 12 weeks and this may reflect the delay in recognizing the pregnancy as well as, the difficulty to access health services.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of complications was higher among women with gestational age above 12 weeks and this may reflect the delay in recognizing the pregnancy as well as, the difficulty to access health services. In contrast of this, other studies observed that complications were more frequent in early abortions 9,12 .…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This is similar to other studies which found that increasing gestational age was associated with an increased risk of severe complication following induced abortion. 7,8 In our series, abortionists were mainly untrained health providers (nurses) in the SC group (49/76 or 64.5%) as already observed by others. 4,9 Abortions were performed mainly at abortionist's or patient's home (41.6%), in a health center (35.1%), in a private clinic (21.2%) and rarely in a hospital (2.1%).…”
Section: Discussionsupporting
confidence: 52%